2014
DOI: 10.1038/eye.2014.283
|View full text |Cite
|
Sign up to set email alerts
|

We need to pay heed to the psychosocial aspects of strabismus

Abstract: Adult strabismus surgery has long been regarded as cosmetic. This paper summarises the current evidence that this statement should be discarded. The evidence shows that strabismus surgery in non-diplopic adult patients can be beneficial in both functional and psychological situations. It is suggested that the term cosmetic would be better replaced by reconstructive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…For reading function, Surgery group reached values very close to the healthy Control group. This is in accordance with other studies that emphasize the reconstructive character of strabismus surgery and suggest not to use the term cosmetic, because of its potential impact on functions (Marsh, 2015;Mollenhauer & Haase, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For reading function, Surgery group reached values very close to the healthy Control group. This is in accordance with other studies that emphasize the reconstructive character of strabismus surgery and suggest not to use the term cosmetic, because of its potential impact on functions (Marsh, 2015;Mollenhauer & Haase, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Other authors found increases of nearly all psychosocial dimensions used in their study (Alpak et al, 2014). Marsh reports very similar results in his overview (Marsh, 2015).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…When there is no diplopia present, realignment surgery is regarded as a cosmetic procedure and therefore is not always covered by insurance (Marsh, 2014), but the American Association for Pediatric Ophthalmology and Strabismus (AAPOS) argues that strabismus surgery is reconstructive, not cosmetic, and that most insurance companies should cover the cost (American Association for Pediatric Ophthalmology and Strabismus, 2019). The appearance of strabismus is associated with a variety of negative psychosocial consequences.…”
Section: Quality Of Lifementioning
confidence: 99%